DISCOVERY LEARNING ACTIVITIES AS AN ALTERNATIVE MODEL IN TEACHING READING AT SMAN 1 KOMODO - Jedina, Maria Goreti (Publikasi dan UKI Press UKI Toraja., 2022)
This research employed quasi experimental design. The population of this research was the second-grade students at SMAN 1 Komodo in 2021/2022 academic year. This research used cluster random sampling. The sample of this research consisted of 72 students in which 37 students in control group and 35 students in experimental group. The research data were collected by using reading comprehension test which was analyzed by descriptive and inferential statistic through SPSS version 16 for windows 7 32 bit. The students’ result of posttest of experimental group more significantly improved than the students’ result of posttest of control group by the mean score 69.14 > 46.12. The difference of both scores is statistically significant based on the t-test value at significant level 0.05 in which the probability value is longer than the significant level (0.00 < 0.05). Then the results of the pre-test showed that the p-Value (probability value) was higher than (0.46 and 0.48 > 0.05) and the degree of freedom was 70. While the post-test p-Value of the two groups was lower than (0.00 < 0 0.05) and 70 degrees of freedom. The t-test scores of the two groups in the post-test were significantly different. This shows that the alternative hypothesis (H1) is accepted and of course the null hypothesis (H0) is rejected. It was concluded that the use of Discovery Learning is effective to be implemented in improving the students’ reading comprehension focusing on literal, inferential and critical comprehension